Single-longitudinal-mode Ho:LuAG laser at 2.1 μm. (23rd December 2015) - Liu, W; Ju, Y L; Dai, T Y; Cui, Z; Wu, J; Yao, B Q; Duan, X M; Shen, Y J; Wang, Y Z
Abstract: In this letter we report a continuous wave Ho:LuAG laser running on single-longitudinal-mode operation. Two Fabry–Perot etalons were used to narrow the laser line-width. By regulating the angle of the etalons, single-longitudinal-mode lasing was achieved at a wavelength of 2100.65 nm. The maximum power and the slope efficiency of single-longitudinal-mode Ho:LuAG output are 264 mW and 14.5%, respectively. To our knowledge, this is the first time a Ho:LuAG laser with single-longitudinal-mode operation has been obtained.